2003
DOI: 10.1212/01.wnl.0000094823.74175.92
|View full text |Cite
|
Sign up to set email alerts
|

1 Hz rTMS enhances extrastriate cortex activity in migraine

Abstract: We recently reported a paradoxical facilitatory effect of 1 Hz repetitive TMS (rTMS) on the primary visual cortex in migraine possibly due to the failure of inhibitory circuits, unable to be upregulated by low frequency rTMS. To investigate if inhibitory circuit dysfunction extends beyond striate cortex in migraine with aura, we studied the effects of 1 Hz rTMS over the right extrastriate cortex on perception of illusory contours in these patients. Low-frequency rTMS enhanced activity of extrastriate cortex in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 9 publications
2
41
0
1
Order By: Relevance
“…In visual cortex, the deficiency of the inhibitory tone was suggested to explain the lack of inhibitory effects to single pulse TMS [28] and the paradoxical facilitation to 1 Hz rTMS [13,29]. In motor cortex, more direct evidence on the activity of inhibitory circuits has been achieved by techniques like paired pulse stimulation [14] or cortical silent period [30][31][32] that allow exploration of GABA Aand GABA B -mediated circuits.…”
Section: Discussionmentioning
confidence: 99%
“…In visual cortex, the deficiency of the inhibitory tone was suggested to explain the lack of inhibitory effects to single pulse TMS [28] and the paradoxical facilitation to 1 Hz rTMS [13,29]. In motor cortex, more direct evidence on the activity of inhibitory circuits has been achieved by techniques like paired pulse stimulation [14] or cortical silent period [30][31][32] that allow exploration of GABA Aand GABA B -mediated circuits.…”
Section: Discussionmentioning
confidence: 99%
“…In another study with rTMS in MwA patients, a failure of inhibitory circuits also involving the extrastriate cortex was reported. 19 A study by Afra et al 5 showing occipital hypoexcitability rather than hyperexcitability in MwA patients was later criticized by Aurora and Welch 36 In their letter they suggested that this controversy might be explained by different methods used in different studies (i.e. type of stimulator, size of coil, intensity of the stimulus).…”
Section: Discussionmentioning
confidence: 99%
“…Motor symptoms in some migraine subtypes have also drawn attention to the hyperexcitability of motor cortex. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Transcranial magnetic stimulation (TMS) is a non-invasive tool to investigate physiology and excitability of both motor-and occipital cortices. 11,[21][22][23][24][25] The changes in motor threshold, latency and amplitude of motor evoked potential, central motor conduction time and cortical silent period after magnetic ABSTRACT: Objective: We evaluated motor and occipital cortex excitability in migraine patients using transcranial magnetic stimulation.…”
mentioning
confidence: 99%
“…This theory is supported by a study in 2001, demonstrating that after Transcranial Magnetic Stimulation, MA patients were more susceptible to hyperexcibility in the visual cortex than controls, indicating that MA patients may have a lower level of inhibition in the cerebral cortex than control subjects (Mulleners et al, 2001). Other studies have suggested that this lack of inhibition may be due to defective gamma-aminobutyric acid (GABA) circuits (Palmer et al, 2000;Fierro et al, 2003) Decreased GABA A receptor activation and expression has been demonstrated in several studies to result in decreased inhibition within the brain (Storer et al, 2001(Storer et al, , 2004Schiene et al, 1996), suggesting that GABA receptor activation and expression may be decreased in individuals with migraine.…”
Section: Introductionmentioning
confidence: 89%